STRATEGI PROMOSI DALAM MEMBANGUN BRAND MEDIA MANDIRI (STUDI KASUS DONATUR MEDIA MANDIRI) - Sifa Isnu, Mei Mila; Khadijah, Siti (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2015)
PT Global Insight Utama is a company engaged in nitrogen gas content services for cars and motorcycles, in a year, the company manage to have 50 booth and 60.000 consumer. In strategic promotional mix study that uses PT. Global Insight Utama in marketing green nitrogen, in achieving tremendeous achievement. The purpose of this study is to defind out what elements of promotional mix used by PT. Global Insight. In marketing green nitrogen, knowing what kinds of messages delivered by PT Global Insight Home in marketing various products nitrogen gas content services to drivers of vehicles, and to know what media is used by the PT. Global Insight Home in marketing green nitrogen. In this research, researcher used descriptive qualitative method. Data collection using in depth interviews, observation, documentation. In order to check the validity of the data triangulation of sources is used. Survey results revealed that the PT. Global Insight Utama Main implementing strategies for marketing promotion mix of green nitrogen to the public. Promotion mix strategy adopted by the PT. Global Insight is to implement the Primary Advertising, Advertising the application itself using the line bellows is by distributing flyers, handing out schedules of fasting, Red vouchers, sponsorship, and free softdrink. Direct marketing by phone, Website, Facebook, and Twitter. Personal Selling, public relations and publicity up today have not been done.